Correction: Patient perspectives on telemedicine during the COVID-19 pandemic: a mixed-methods community-based study - Splinter, Marije J.; Ikram, M. Kamran; Helsper, Charles W.; Bindels, Patrick J. E.; de Schepper, Evelien I. T.; Licher, Silvan (BMC health services research, 2025)
Correction: BMC Health Serv Res 23, 803 (2023) https://doi.org/10.1186/s12913-023-09794-w In this article an incomplete figure appeared as Fig. 1 due to a typesetting mistake. Copy to clipboard Provided by the Springer Nature SharedIt content-sharing initiative Correction Open access Published:28 January 2025 Correction: Patient perspectives on telemedicine during the COVID-19 pandemic: a mixed-methods community-based study Marije J. Splinter 1, M. Kamran Ikram1,2, Charles W. Helsper3, Patrick J. E. Bindels4, Evelien I. T. de Schepper4 & … Silvan Licher1 Show authors BMC Health Services Research volume 25, Article number: 165 (2025) Cite this article Metrics details The Original Article was published on 27 July 2023 Correction: BMC Health Serv Res 23, 803 (2023) https://doi.org/10.1186/s12913-023-09794-w In this article an incomplete figure appeared as Fig. 1 due to a typesetting mistake.